2020
DOI: 10.21037/tau-20-474
|View full text |Cite
|
Sign up to set email alerts
|

Open partial nephrectomy: current review

Abstract: Partial nephrectomy (PN) is increasingly considered the gold standard treatment for localized renal cell carcinomas (RCCs) where technically feasible. The advantage of nephron-sparing surgery lies in preservation of parenchyma and hence renal function. However, this advantage is counterbalanced with increased surgical risk. In recent years with the popularization of minimally invasive partial nephrectomy (laparoscopic and robotic), the contemporary role of open PN (OPN) has changed. OPN has several advantages,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 73 publications
(82 reference statements)
0
12
0
Order By: Relevance
“…4 Although multiple studies [5][6][7] at various levels of evidence have demonstrated non-inferiority of cryoablation, percutaneous cryoablation (PCA) in particular, in some subgroups or under specific scenarios, PN should still be taken into primary consideration due to its efficacy in maximizing renal function and minimizing preoperative complications based on a large body of clinical evidence at present. [8][9][10] With advances in devices and procedures, PN has undergone a continuous improvement process from open partial nephrectomy (OPN) to minimally invasive strategies including laparoscopic partial nephrectomy (LPN) and robotassisted partial nephrectomy (RAPN). 11,12 Therein, RAPN shows an increasingly preferred trend to be applied in resection of more complex tumours and preservation of more renal parenchyma due to its increased dexterity, improved visualization and surgical precision.…”
Section: Introductionmentioning
confidence: 99%
“…4 Although multiple studies [5][6][7] at various levels of evidence have demonstrated non-inferiority of cryoablation, percutaneous cryoablation (PCA) in particular, in some subgroups or under specific scenarios, PN should still be taken into primary consideration due to its efficacy in maximizing renal function and minimizing preoperative complications based on a large body of clinical evidence at present. [8][9][10] With advances in devices and procedures, PN has undergone a continuous improvement process from open partial nephrectomy (OPN) to minimally invasive strategies including laparoscopic partial nephrectomy (LPN) and robotassisted partial nephrectomy (RAPN). 11,12 Therein, RAPN shows an increasingly preferred trend to be applied in resection of more complex tumours and preservation of more renal parenchyma due to its increased dexterity, improved visualization and surgical precision.…”
Section: Introductionmentioning
confidence: 99%
“…Renal cell carcinoma is heterogeneous disease which is caused by different histological variants, The most common subtype of renal cell carcinoma is clear cell accounting 75 %, papillary follows about 10 %, chromophobe 5 % and undifferentiated 10 % of all cases. Chromophobe renal cell carcinoma, a distinct subtype of renal cell carcinoma (RCC) with characteristic light microscopic, histochemical, and ultrastructural features [ 3 ].Several risk factors have been identified that are potentially responsible for the increasing number of newly-diagnosed renal cell carcinomas, among them smoking, hypertension, age, and male gender [ 4 ].Renal cell carcinoma can be diagnosed based on clinical presentation, Common presenting complaints and signs included: abdominal pain, hematuria, abdominal mass, and other symptoms, including decreasing renal function, proteinuria, and pain from metastatic site, they can be asymptomatic and are discovered while worked-up for other medical problems [ 5 ].Contrast-enhanced computed tomography (CT) detects 90 % of renal masses, identifies benign and pathologic features, and evalu¬ates surrounding anatomy to detect lymphadenopathy or an associated thrombus, For incompletely characterized masses or contraindica¬tions to CT, magnetic resonance imaging with and without intravenous contrast is recommended [ 6 ].The primary choice of the treatment of any stage of RCC is surgical excision, partial nephrectomy has emerged as the widely recommended treatment for small renal tumors, while Partial nephrectomy was initially reserved for cases with a contraindication to radical nephrectomy, such as solitary kidney, chronic kidney disease and multi-focal or bilateral tumors, it has now become the surgical gold standard for all small renal tumors when technically feasible, The advantage of nephron-sparing surgery lies in preservation of parenchyma and hence renal function [ 7 ].Studies that investigate the results of systemic therapies in patients diagnosed with metastatic Chromophobe RCC disease suggest that sunitinib have an advantage compare to everolimus without being statistically significant, and sunitinib seems to be superior than sorafenib, but the optimum therapy for Chromophobe RCC is still missing [ 8 ].Several large studies have indicated that prognosis of chromophobe RCC is much better than that of clear cell RCC and papillary RCC. Most chromophobe RCC have a favorable outcome and low risk of metastasis, but there is evidence that chromophobe RCC have a predisposition to metastasise into the liver [ 1 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Modification of immunosuppression to m-TOR inhibitors is an adequate measure in such patients [ 13 ]. It is important to note, however, that open partial nephrectomy in patients with renal transplant has greater technical challenges for achieving vascular control due to the presence of adhesions of the renal hilum [ 14 ].…”
Section: Discussionmentioning
confidence: 99%